Creating private criteria for A-CDM effectiveness to take into account the interests of decision-making participants in a dynamic environment - G. N. Lebedev; V. B. Malygin (Научный вестник МГТУ ГА, 2020)
We consider the problem of collaborative decision making of the production process at airlines (CDM) in dynamically changing conditions of occurrence of emergency situations that make changes in the action plan. In the production process, due to the different orientation of the tasks to be solved, the solution may require a large or small number of possible variant solutions. The article presents a concrete example of such a situation affecting the conventional three services of the aviation complex, each with its own interests in the overall production process. The solution to this problem is the only option in favor of the overall production process. For this purpose, several designations and assumptions have been introduced, the list of which can be supplemented. Dynamic priorities are defined for each participant of the process. Optimization of collaborative decision-making can be achieved either by a simple search for solutions, or by using a genetic algorithm that allows you to get a suboptimal solution that meets the requirements of the participants in the process using a smaller number of iterations in real time. In this example, we consider a situation that occurs in a real enterprise due to bad weather conditions. Thus, dynamic priorities are assigned based on a multiplicative form for delayed flights, considering the interests of participants in the process, private criteria are formed for ranking flights at each step of rescheduling, and a genetic algorithm is applied. As a result, we obtained four solutions to the disruption caused by external factors. The first three options correspond to the interests of three parties concerned, and the fourth one is consolidated. All the solutions were different, which indicates the need for an objective and reasonable decision-making apparatus for joint management of the production process. The proposed mathematical apparatus has this ability and prospects for implementation.